Spa Services State Distribution and Spa Specialization in Małopolskie Communes - Stelmach , Paweł (Studia Oeconomica Posnaniensia, 2018)
The aim of the paper is to identify and explain the relation between spa service state distribution and spa specialization in Małopolskie voivodeship communes. Correlation and regression analyses were applied based on data from the Local Data Bank and unpublished sets from the Central Statistical Office of Poland. To explain the identified relations, the time series of indicators of spa service state distribution, spa specialization, nights spent and share of state subsidized nights in total nights were analyzed. In two of six of the researched areas (Uście Gorlickie and Kraków) exists a functional relationship between spa service state distribution and spa specialization. The Uście Gorlickie area shows the highest level of uncertainty associated with the state distribution channel.